1989
DOI: 10.1111/j.1432-1033.1989.tb14722.x
|View full text |Cite
|
Sign up to set email alerts
|

Purine and pyrimidine nucleotides potentiate activation of NADPH oxidase and degranulation by chemotactic peptides and induce aggregation of human neutrophils via G proteins

Abstract: Whereas the chemotactic peptide, N-formyl-L-methionyl-L-leucyl-L-phenylalanine (Met-Leu-Phe), induced NADPH-oxidase-catalyzed superoxide (0;) formation in human neutrophils, purine and pyrimidine nucleotides per se did not stimulate NADPH oxidase but enhanced 0; formation induced by submaximally and maximally stimulatory concentrations of Met-Leu-Phe up to fivefold. On the other hand, Met-Leu-Phe primed neutrophils to generate 0; upon exposure to nucleotides. At a concentration of 100 pM, purine nucleotides en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 53 publications
0
48
0
1
Order By: Relevance
“…With respect to O2" formation in Bt2cAMP-differentiated HL-60 cells, both nucleotides are similarly potent (22). Differences concerning the potency and/or effectiveness of purine and pyrimidine nucleotides to activate various cell functions were also observed in human neutrophils (6). We did not analyze in detail the structure/activity relationship of purine and pyrimidine nucleotides with respect to Ca 2+ mobilization, but this may be an interesting task for future studies.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…With respect to O2" formation in Bt2cAMP-differentiated HL-60 cells, both nucleotides are similarly potent (22). Differences concerning the potency and/or effectiveness of purine and pyrimidine nucleotides to activate various cell functions were also observed in human neutrophils (6). We did not analyze in detail the structure/activity relationship of purine and pyrimidine nucleotides with respect to Ca 2+ mobilization, but this may be an interesting task for future studies.…”
Section: Discussionmentioning
confidence: 97%
“…All cell culture media were obtained from Biochrom (Berlin, FRG). Sources of other materials have been described elsewhere (6,7,22,25,26).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Labasi et al [26] show that neutrophils from wild-type or P2X 7 R-deficient mice did not change shape and lack L-selectin shedding in response to ATP, suggesting the absence of surface expression of P2X 7 R. Other groups have found that differentiated HL-60 cells show expression of P2X 7 R, but their function (measured as an increase in intracellular Ca 2+ after stimulation with ATP) is not changed during development [1]. Finally, it has been reported that ATP by itself is unable to generate ROS in human neutrophils and differentiated HL-60 cells [39,43] and that P2X 7 R are stored in intracellular organelles susceptible for recruitment to plasma membrane after neutrophil activation [19]. In our hands, however, activation of human neutrophils (judged by cell migration and changes in cell morphology) with fMLP did not result in ATP-activated currents.…”
Section: Discussionmentioning
confidence: 99%